Pengaruh Kebijakan Dividen Terhadap Harga Saham - Herman Sjahruddin; Muh. Akob Kadir; Andi Selfi; Muh. Agung Permana (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This study aims to examine dividend policy on stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). Data collection using periodic data obtained from the 2019- 2021 financial statements with purposive sampling techniques, the number of company samples is 13 companies so 42 analysis data are obtained. The results of the financial statements obtained have gone through classical assumptions. The data analysis method uses regression analysis panel data model Common Effect Model (CEM) using Eviews 12. The research results from the test are that the Dividend Policy has a negative and significant effect on Stock Price. The results of the Coefficient of Determination show an R-squared value of 0.252303, the results explain that the ability of the independent variable to explain the dependent variable is 25.23%, while the remaining 74.77% is influenced by other factors that are not found in this research model. Keywords: Dividend payout ratio, food and beverage sub-sector, Stock Price